Effect of Yoga on Blood Pressure in Prehypertension: A Systematic Review and Meta-Analysis - Janhavi Sandeep Khandekar; Vanamala Lakshmi Vasavi; Vijay Pratap Singh; Stephen Rajan Samuel; S. G. Sudhan; Bidita Khandelwal (The Scientific World Journal)
Introduction. Prehypertension is a precursor for developing hypertension and is a risk factor for cardiovascular diseases. Yoga therapy may have a role in lowering the blood pressures in prehypertension and hypertension. This systematic review aims to synthesize the available literature for the same. Methodology. Databases such as PubMed, Embase, Scopus, and Web of Science were searched for randomised control trials only in the time duration of 2010–2021. The main outcome of interest was systolic and diastolic blood pressures. Articles were screened based on the inclusion criteria, and 8 articles were recruited for the review. Meta-analysis was done for suitable articles. RevMan 5.4 by Cochrane was used for meta-analysis and forest plot construction. Risk of bias was determined using the Downs and Black checklist by three independent authors. Results. The meta-analysis of the articles favoured yoga intervention over the control intervention. Yoga therapy had significantly reduced the systolic pressure (−0.62 standard mean difference, at IV fixed 95% CI: −0.83, −0.41) and diastolic pressure (−0.81 standard mean difference, at IV random 95% CI: −1.39, −0.22). Secondary outcome measures studied were heart rate, weight, BMI, waist circumference, and lipid profile. The main protocol of yoga therapy included postures, breathing exercises, and different meditation techniques. A significant reduction in secondary outcomes was observed, except for HDL values in lipid profile which showed a gradual increase in yoga group in comparison with alternative therapy. Conclusion. Yoga therapy has shown to be significant in the reduction of systolic and diastolic pressure in prehypertensive population. Supporting evidence lacks in providing a proper structured dosage of yoga asanas and breathing techniques. Considering the existing literature and evidence, Yoga therapy can be used and recommended in prehypertensive population and can be beneficial in reducing the chances of developing hypertension or cardiovascular diseases.